The Death Of Captain America Represents The Failure Of The American Dream - Anggara, Dimas (UI Scholars Hub, 2014)
American Dream is a concept that plays an important role in the American history and its society. The main values of the American Dream are life, liberty, and pursuit of happiness. These are represented in Captain America, carrier of the spirit of America to the world. Captain America, the main character in a comic, also preserved the values in the American Dream, so it is proven that there is a relation between Captain America and the American Dream. The problem is that there are changes in the way people see the concept of the American Dream today. It is because many people tend to simplify the values in which the concept off ers. This paper examines the relation between the change of perspective and the way the people in the U.S in applying the American Dream with the death of Captain America as the representation of the American Dream. This paper argues that the Death of Captain America can be a representation of the failure in the concept because Captain America died defending what he believed as the true American Dream that all the people in the U.S should preserve. Thus, many people believe the values which Captain America preserved are no longer suitable in the society today.